Wybrane strategie werbalne w przekazach elektronicznych na przykładzie blogu (Conversatoria Linguistica, 2019)
Blog as a genre of the text is linked to an electronic message generated in cyberspace. Blog is a place of confrontation and dialogue. The presented examples are a testament to saturation strategy verbal multimedia graphic elements. The texts of blog is a conglomerate of verbal communication and audiovisual items. The analysis shows that this drastic confrontation does not always equal to the conflict. Strategies verbal shaped at the level of electronic communication is characterized by nonlinearity associated with the substitution of reading linear navigation. It appears that it is an element of deep cultural change. Printed word has been the transformation - was an open structure (into the Internet eliminates the physical aspect of the press). New media has created a virtual space, in which verbal communication is located within the traditional forms of communication is subject to digitize, creating a stream of information on the foundation of a new fixation – in the area of your computer screen.